Preparation method of ceramic membrane based on algae-containing sludge endogenous pore forming and catalysis

Ultrafiltration ceramic membranes are prepared by the water supply plant containing algae sludge, which solves the problem of traditional ceramic membranes lacking catalytic function and high cost, and achieves efficient removal of pollutants in water and sludge during algae outbreak.

CN120115016AActive Publication Date: 2025-06-10兰溪市钱江水务有限公司 +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510424812.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-07
Publication Date
2025-06-10
Estimated Expiration
2045-04-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively treat algae-containing sludge in water supply plants, and traditional ceramic membranes lack catalytic functions, high cost and complex process.

Method used

The water supply plant's algae-containing sludge is used as raw material, and ultrafiltration ceramic membranes with catalytic and filtration functions are prepared through steps such as drying, ball milling, screening, pre-carbonization, dry press forming, sintering and activation.

Benefits of technology

The prepared ceramic membrane has both ultrafiltration and catalytic properties, which can effectively remove oxidant pollutants in water, and solve the problem of difficult treatment of sludge in water supply plants during the algae outbreak period, reducing costs and process complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120115016A_ABST
    Figure CN120115016A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of environmental functional materials and water treatment, and aims to provide a preparation method of a ceramic membrane based on algae-containing sludge endogenous pore forming and catalysis. Comprising the following steps: drying, ball-milling and screening dewatered sludge of a water supply plant in a water source algae outbreak period to obtain sludge powder; organic acid with complexing capacity is used as a heavy metal removing agent for soaking treatment and then is cleaned, and a diaphragm is obtained through pre-carbonization treatment, dry pressing blank making and sintering forming; and performing primary activation treatment in weak oxidizing strong acid, performing heating treatment after washing, and performing secondary activation to obtain an ultrafiltration ceramic membrane product. The method is simple in operation steps, easy to implement, green and environmentally friendly; the prepared ceramic membrane has good separation performance and high mechanical strength, can catalyze a common oxidant for water treatment while filtering, and can generate free radicals for degrading organic matters through decomposition; or a common cleaning agent sodium hypochlorite is catalyzed during membrane cleaning, and free radicals are generated, so that the cleaning effect is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of environmental functional materials and water treatment, and particularly relates to a method for preparing a catalytic ceramic membrane by using endogenous components (algae, manganese oxides, and aluminum salt flocs) in algae-containing sludge from waterworks, which is applicable to scenarios such as drinking water purification and medical wastewater treatment. Background Art

[0002] The coupling of membrane separation and catalytic oxidation is a cutting-edge technology in water treatment. A separation membrane with both catalytic and filtration functions can not only efficiently remove pollutants in water but also achieve self-cleaning of the fouled membrane, which is one of the research hotspots in the current water treatment field. Traditional ceramic membranes are made of pure-phase inorganic substances such as kaolin, Al 2 O 3 , TiO 2 , ZrO 2 and SiO 2 etc. as raw materials, which are costly and lack catalytic functions. If catalytic functions are required, additional catalysts need to be loaded, and the process is complex.

[0003] The problem of the outbreak of water source algae in certain seasons is a common problem faced by many waterworks that use lake and reservoir water as water sources. During the algae outbreak period, waterworks usually add permanganate at the water intake to strengthen algae removal, odor removal, and control of algal toxins. Therefore, at this time, the sludge in the waterworks contains not only these components but also algae, manganese oxides, etc. This has brought great difficulties to the subsequent sludge disposal. If these sludges are treated by the traditional landfill method, it is easy to cause the release of algal toxins and the leakage of manganese ions. Therefore, the disposal problem of algae-containing sludge from waterworks is also an urgent problem to be solved in the current water supply industry.

[0004] Therefore, the present invention intends to propose a new solution to solve the above problems. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a ceramic membrane based on endogenous pore formation and catalysis of algae-containing sludge.

[0006] To solve the technical problem, the solution of the present invention is:

[0007] Provide a method for preparing an ultrafiltration ceramic membrane with both catalytic and filtration functions, including the following steps:

[0008] (1) Take the dehydrated sludge from the waterworks during the algae outbreak period of the water source, and obtain sludge powder after drying, ball milling, and screening.

[0009] (2) Use an organic acid with complexing ability as a heavy metal remover to soak the sludge powder; then wash it with deionized water and air-dry it naturally.

[0010] (3) In an anaerobic atmosphere, perform pre-carbonization treatment on the air-dried sludge powder;

[0011] (4) Mold the pre-carbonized sludge powder by dry pressing to prepare a green sludge embryo;

[0012] (5) Heat up the green sludge embryo and sinter it to form a membrane;

[0013] (6) Place the sintered membrane in a weakly oxidizing strong acid and perform preliminary activation treatment by circulating filtration; then change to circulating filtration with deionized water and rinse until the conductivity remains unchanged, take it out and air-dry it at room temperature;

[0014] (7) Under vacuum conditions, heat-treat the air-dried membrane for secondary activation to obtain an ultrafiltration ceramic membrane product.

[0015] As a preferred embodiment of the present invention, in the step (1), the organic matter content in the sludge is 35% - 50%; the drying temperature is 105 - 120 °C, and the drying time is ≥ 24 h; the particle size range of the sludge powder obtained by ball milling and screening is 6.5 - 10 μm.

[0016] As a preferred embodiment of the present invention, in the step (2), the organic acid is citric acid or oxalic acid with a mass concentration of 5.5% - 10%, and the soaking time is 24 - 36 h.

[0017] As a preferred embodiment of the present invention, in the step (3), continuously introduce nitrogen or helium into the tubular furnace to form an anaerobic atmosphere; the temperature of the pre-carbonization treatment is 350 - 450 °C, and the time is 3 - 5 h.

[0018] As a preferred embodiment of the present invention, in the step (4), during the dry pressing process, control the pressure to be 20 - 25 Mpa.

[0019] As a preferred embodiment of the present invention, in the step (5), use a heating controller to perform programmed heating, the heating rate is 5 - 15 °C / min, the sintering temperature is 1000 - 1200 °C, and the sintering time is 1.5 - 2 h.

[0020] As a preferred embodiment of the present invention, in the step (6), the strong acid used for preliminary activation is hydrochloric acid with a concentration of 0.1 - 0.2 mol / L, and the activation treatment time is 3 - 4 h.

[0021] As a preferred embodiment of the present invention, in the step (7), the temperature during secondary activation is 250 - 400 °C, and the activation time is 2 - 2.5 h.

[0022] The present invention further provides a method for water treatment using the ultrafiltration ceramic membrane prepared by the aforementioned method, which is to use the ultrafiltration ceramic membrane as a filtering component of a filtering device or a purification device; introduce the drinking water, sewage or wastewater to be treated into the filtering device or the purification device, and the water flow passes through the ultrafiltration ceramic membrane with the contact time during actual filtration being at least 8 seconds; while intercepting particulate pollutants through the micropores on the ultrafiltration ceramic membrane, catalytic decomposition treatment is carried out on oxidant pollutants in the water.

[0023] As a preferred embodiment of the present invention, the oxidant pollutants refer to residual oxidants used for water treatment, specifically any one or more of the following: sodium hypochlorite, chlorine dioxide, chloramine, ozone, hydrogen peroxide, monopersulfate, persulfate, peracetic acid, sodium percarbonate, permanganate, ferrate.

[0024] Description of the invention principle:

[0025] 1. Compared with the sludge from wastewater treatment plants, the sludge from water treatment plants has relatively simple and stable components, mainly including minerals such as alumina, iron oxide, and calcium oxide, and also contains a certain proportion of organic matter, water, and ash. Most water treatment plants landfill the dehydrated sludge as waste, or simply recycle the coagulant to make building materials such as ceramsite and ceramic tiles, but such applications do not fully realize the high-value resource utilization of sludge. The research team of the applicant has found through long-term in-depth research that the components of the sludge from water treatment plants are relatively close to the raw material components required for preparing ceramic membranes. Using the sludge from water treatment plants as the raw material for ceramic membranes is a very beneficial and highly feasible attempt.

[0026] 2. The present invention mainly puts forward innovative ideas from the following aspects: (1) Innovation in raw material utilization: directly use the sludge from water treatment plants during the algae bloom period without exogenous additives (skeleton materials, pore-forming agents, etc.), and the cost is significantly reduced compared with traditional ceramic membranes. (2) Innovation in endogenous functions: Algae in the sludge form micropore precursors through pre-carbonization under nitrogen protection at 300 °C (uniform pores are left after its high-temperature calcination and gasification); the iron, manganese, and aluminum components in the sludge are protected by reducing carbon during the high-temperature sintering process, which can reduce the oxygen coordination degree of metal elements and improve the catalytic activity of the ceramic membrane; Fe 2 O 3 、Al 2 O 3 and other oxides form spinel structures with manganese ions and oxides through high-temperature sintering, which can significantly improve the mechanical strength of the ceramic membrane. (3) Innovation in process: adopt a heat treatment process of low temperature - high temperature - vacuum low temperature, and then combine acid washing to enhance the active sites. (4) Innovation in the functions of the finished membrane material: The ceramic membrane prepared by the present invention has both ultrafiltration performance (average pore diameter < 100 nm) and catalytic performance.

[0027] Based on the bottleneck problems in the treatment of algae-containing sludge in comprehensive water treatment plants and the innovative ideas in the preparation of ceramic membranes, the present invention proposes a method for preparing ultrafiltration ceramic membranes with both catalytic and filtration functions using inexpensive algae-containing sludge from water treatment plants. The micropores (porosity 45%-50%) are generated by the carbonization of algae, replacing the externally added pore-forming agent; the Mn oxides in the sludge act as catalysts, which can catalyze the production of reactive free radicals by conventional water treatment oxidants such as hypochlorite, chlorine dioxide, ozone, etc.; the aluminum salt flocs and manganese ion oxides form a spinel structure (MnAl 2 O 4 ), enhancing the compressive strength of the membrane.

[0028] 3. The key points of the present invention different from the prior art are: (1) When the prior art uses sludge to prepare ceramic membranes, it usually only considers the filtration performance as the core index, while the product of the present invention has both catalytic and filtration performances; (2) To meet the requirements of the product structure strength, in addition to using the sludge itself, the prior art usually needs to add additional auxiliary materials during the preparation process, such as kaolin, clay, organic pore-forming agents (wood chips, starch, etc.); the present invention does not need to add any materials other than the sludge itself, and completely relies on the precise and ingenious regulation of the preparation process to achieve the required functions; (3) The existing catalytic membrane technology completely relies on external catalysts, and the added catalytic components are often precious metals, with high costs. The present invention cleverly utilizes the roles of iron, manganese, and aluminum components in the sludge during the high-temperature sintering process to improve the catalytic activity of the ceramic membrane without adding any precious metal catalysts.

[0029] Compared with the prior art, the technical effects of the present invention are:

[0030] 1. The preparation method of the inorganic catalytic filtration ceramic membrane provided by the present invention has simple operation steps, is easy to implement, and is green and environmentally friendly;

[0031] 2. The ceramic membrane prepared by the present invention has good separation performance and high mechanical strength, and can catalyze the oxidants commonly used in water treatment during filtration, and the generated free radicals are used to degrade organic substances after decomposition; or catalyze the common cleaning agent sodium hypochlorite during membrane cleaning to generate free radicals, thereby enhancing the cleaning effect.

[0032] 3. The present invention solves the problems of high cost and large energy consumption existing in the current ceramic membrane preparation technology, and can actually solve the problem of difficult treatment of sludge in water treatment plants during the algae bloom period. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is the pore size distribution diagram of the ceramic membrane prepared by the present invention;

[0034] Figure 2 It is the catalytic performance diagram of the ceramic membrane prepared by the present invention. DETAILED DESCRIPTION OF THE INVENTION

[0035] The following will describe in detail the specific implementation manners of the present invention in conjunction with the accompanying drawings.

[0036] Part I: Implementation Scheme of the Present Invention

[0037] A preparation method of an ultrafiltration ceramic membrane with both catalytic and filtration functions according to the present invention includes the following steps:

[0038] (1) Take the dewatered sludge from a waterworks during the period of algal bloom in the water source, and after drying, ball milling and screening, obtain sludge powder; the organic matter content in the sludge is 35% - 50%; the temperature of the drying treatment is 105 - 120 °C, and the drying time is ≥ 24 h; the particle size range of the sludge powder obtained by ball milling and screening is 6.5 - 10 μm.

[0039] The sludge is selected from the dewatered sludge of a waterworks during the period of algal bloom in the water source, and the micro - pores generated by the carbonization of algae can be utilized to replace the externally added pore - forming agent; the sludge is treated to ensure the removal of free water and bound water in the sludge. After drying the sludge, ball milling and screening are carried out to control the particle size of the powder, which can not only ensure that the prepared ceramic membrane has a suitable pore size, but also ensure its good porosity and permeability.

[0040] (2) Use an organic acid with complexing ability as a heavy - metal remover to soak the sludge powder; then wash it with deionized water and air - dry it naturally; the organic acid is citric acid or oxalic acid with a mass concentration of 5.5% - 10%, and the soaking time is 24 - 36 h.

[0041] To avoid the influence of impurity heavy metals on the catalytic activity, mild organic acids such as citric acid and oxalic acid are used to remove harmful heavy metals such as Pb and Cd, which can reduce the corrosion of raw materials; control the concentration of the organic acid used for soaking and the soaking time to obtain a better removal effect of harmful heavy metals while minimizing the corrosion of raw materials as much as possible.

[0042] (3) Carry out pre - carbonization treatment on the air - dried sludge powder in an anaerobic atmosphere; continuously introduce nitrogen or helium into the tubular furnace to form an anaerobic atmosphere; the temperature of the pre - carbonization treatment is 350 - 450 °C, and the time is 3 - 5 h.

[0043] The pre - carbonization process is carried out under anaerobic conditions and is achieved by continuously introducing an inert protective gas. Control the temperature and time of the pre - carbonization treatment to retain the algal organic - matter skeleton and remove volatile components, enhancing the stability of the overall structure in subsequent sintering.

[0044] (4) Mold the pre - carbonized sludge powder by dry pressing to prepare a sludge green body; during the dry - pressing molding process, control the pressure to be 20 - 25 Mpa.

[0045] The pre-carbonized sludge powder is formed into a blank by dry pressing, and the pressure during dry pressing is controlled to ensure the porosity and reduce the cracks that occur during the subsequent high-temperature sintering process.

[0046] (5) Heat up the sludge blank and then sinter it to form a membrane; use a heating controller to carry out programmed heating, with a heating rate of 5 - 15 °C / min, a sintering temperature of 1000 - 1200 °C, and a sintering time of 1.5 - 2 h.

[0047] The blank formed by dry pressing needs to be sintered. During the sintering process, by reasonably controlling the heating rate, sintering temperature, and time, a ceramic membrane with higher strength is obtained.

[0048] (6) Place the sintered membrane in a weakly oxidizing strong acid and carry out preliminary activation treatment by circulating filtration; then change to circulating filtration with deionized water and rinse until the conductivity remains unchanged, take it out and air-dry it at room temperature;

[0049] When carrying out preliminary activation of the ceramic membrane, a weakly oxidizing strong acid is used. Optionally, it is hydrochloric acid with a concentration of 0.1 - 0.2 mol / L, and the activation treatment time is 3 - 4 h.

[0050] (7) Carry out secondary activation on the air-dried membrane by heating treatment under vacuum conditions to obtain an ultrafiltration ceramic membrane product.

[0051] Carrying out secondary heating activation under vacuum conditions can generate more oxygen vacancies (characterized by measuring the ratio of lattice oxygen to adsorbed oxygen by X-ray energy spectrum). The temperature during secondary activation is 250 - 400 °C, and the activation time is 2 - 2.5 h.

[0052] The Second Part: Specific Examples and Comparative Examples

[0053] Example 1

[0054] (1) Select the dewatered sludge from a water supply plant in Jinhua City during the period of algal bloom in the water source. The organic matter content in the sludge is 45%. After drying at 105 °C for 24 hours, it is crushed by a ball mill and then screened through a mechanical vibrating sieve to obtain sludge powder with a particle size of 1340 - 2000 mesh (6.5 - 10 μm) for the subsequent preparation of the ceramic membrane;

[0055] (2) Take the sludge powder obtained in step (1), soak it in 7.5% citric acid as a heavy metal remover for 30 hours, and then wash it with deionized water until the conductivity remains unchanged and air-dry it naturally at room temperature;

[0056] (3) Place the sludge powder in step (2) in a tubular furnace, and maintain an anaerobic atmosphere by continuously introducing nitrogen. Set the heating temperature of the tubular furnace to 400 °C and the heating time to 4 hours. After heating, maintain nitrogen protection until it cools down to room temperature;

[0057] (4) Take the sludge powder in step (3) and place it in a tablet press. The pressure of the tablet press is controlled at 20 Mpa and maintained for 10 minutes, and then the pressure is gradually released to obtain a formed green body;

[0058] (5) Take the formed green body in step (4) and place it in a muffle furnace. Set the programmed heating, with a heating rate of 10 °C / min until 1000 °C. Keep at this temperature for 1.5 hours, and then gradually cool down to room temperature;

[0059] (6) Take the sintered and formed membrane in step (5), circulate and filter a 0.1 mol / L dilute hydrochloric acid solution for 4 hours for activation. Subsequently, circulate and filter deionized water until the conductivity is zero, and then air-dry naturally.

[0060] (7) Take the activated ceramic membrane in step (6) and place it in a vacuum drying oven. Conduct vacuum thermal activation at 300 °C for 2 hours to finally obtain a formed ceramic membrane with catalytic function. The average pore size is measured to be 65 - 92 nm, and the product belongs to the ultrafiltration membrane.

[0061] Example 2:

[0062] (1) Select the dewatered sludge from a water supply plant in Huzhou during the period of algal bloom in the water source. The organic matter content in the sludge is 35%. After drying at 120 °C for 30 hours, it is crushed by a ball mill and then screened through a mechanical vibrating sieve to obtain sludge powder with a particle size of 1340 - 2000 mesh (6.5 - 10 μm) for the subsequent preparation of the ceramic membrane;

[0063] (2) Take the sludge powder obtained in step (1), soak it with 5.5% citric acid as a heavy metal remover for 24 hours, and then wash it with deionized water until the conductivity remains unchanged and air-dry naturally at room temperature;

[0064] (3) Take the sludge powder in step (2) and place it in a tubular furnace. Keep an anaerobic atmosphere by continuously passing helium gas. Set the heating temperature of the tubular furnace to 350 °C and the heating time to 3 hours. After heating, keep nitrogen protection until it cools down to room temperature;

[0065] (4) Take the sludge powder in step (3) and place it in a tablet press. The pressure of the tablet press is controlled at 23 Mpa and maintained for 10 minutes, and then the pressure is gradually released to obtain a formed green body;

[0066] (5) Take the formed green body in step (4) and place it in a muffle furnace. Set the programmed heating, with a heating rate of 5 °C / min until 1100 °C. Keep at this temperature for 1.8 hours, and then gradually cool down to room temperature;

[0067] (6) Take the sintered and formed membrane in step (5), circulate and filter a 0.15 mol / L dilute hydrochloric acid solution for 3 hours for activation. Subsequently, circulate and filter deionized water until the conductivity is zero, and then air-dry naturally.

[0068] (7) Take the activated ceramic membrane in step (6) and place it in a vacuum drying oven. Activate it thermally under vacuum at 250 °C for 2.5 hours to finally obtain a formed ceramic membrane with catalytic function. The average pore size is measured to be 40 - 75 nm, and the product belongs to the ultrafiltration membrane.

[0069] Example 3:

[0070] (1) Select the dewatered sludge from a waterworks in Jiaxing during the period of algal bloom in the water source. The organic matter content in the sludge is 50%. After drying at 110 °C for 36 hours, crush it with a ball mill and then screen it through a mechanical vibrating sieve to obtain sludge powder with a particle size of 1340 - 2000 mesh (6.5 - 10 μm) for the subsequent preparation of the ceramic membrane;

[0071] (2) Take the sludge powder obtained in step (1), soak it in 10% citric acid as a heavy metal remover for 36 hours, then wash it with deionized water until the conductivity remains unchanged and air-dry it naturally at room temperature;

[0072] (3) Take the sludge powder in step (2) and place it in a tubular furnace. Keep an anaerobic atmosphere by continuously passing nitrogen. Set the heating temperature of the tubular furnace to 450 °C and the heating time to 5 hours. After heating, keep the nitrogen protection until it cools down to room temperature;

[0073] (4) Take the sludge powder in step (3) and place it in a tablet press. Control the pressure of the tablet press at 20 Mpa for 10 minutes and then gradually release the pressure to obtain a formed green body;

[0074] (5) Take the formed green body in step (4) and place it in a muffle furnace. Set the programmed heating, with a heating rate of 15 °C / min until 1200 °C, keep it at this temperature for 2 hours, and then gradually cool it down to room temperature;

[0075] (6) Take the sintered and formed membrane in step (5), circulate and filter a 0.2 mol / L dilute hydrochloric acid solution to activate it for 3.5 hours. Subsequently, circulate and filter deionized water until the conductivity is zero, and then air-dry it naturally.

[0076] (7) Take the activated ceramic membrane in step (6) and place it in a vacuum drying oven. Activate it thermally under vacuum at 400 °C for 2 hours to finally obtain a formed ceramic membrane with catalytic function. The average pore size is measured to be 45 - 82 nm, and the product belongs to the ultrafiltration membrane.

[0077] Example 4

[0078] (1) Select the dewatered sludge from a waterworks in Jinhua during the period of algal bloom in the water source. The organic matter content in the sludge is 45%. After drying at 105 °C for 24 hours, crush it with a ball mill and then screen it through a mechanical vibrating sieve to obtain sludge powder with a particle size of 1340 - 2000 mesh (6.5 - 10 μm) for the subsequent preparation of the ceramic membrane;

[0079] (2) Take the sludge powder obtained in step (1), soak it in 7.5% oxalic acid as a heavy metal remover for 30 hours, then wash it with deionized water until the conductivity remains unchanged and air-dry it naturally at room temperature;

[0080] (3) Take the sludge powder in step (2) and place it in a tubular furnace. Keep an anaerobic atmosphere by continuously passing nitrogen. Set the heating temperature of the tubular furnace to 400 °C and the heating time to 4 hours. After heating, keep the nitrogen protection until it cools down to room temperature;

[0081] (4) Take the sludge powder in step (3) and place it in a tablet press. Control the pressure of the tablet press at 25 Mpa, hold for 10 minutes and then gradually release the pressure to obtain a formed green body;

[0082] (5) Take the formed green body in step (4) and place it in a muffle furnace. Set the programmed temperature rise, with a heating rate of 10 °C / min until 1000 °C. Keep it at this temperature for 1.5 hours, and then gradually cool it down to room temperature;

[0083] (6) Take the sintered and formed membrane in step (5), circulate and filter a 0.1 mol / L dilute hydrochloric acid solution for 4 hours of activation. Subsequently, circulate and filter deionized water until the conductivity is zero, and then air-dry it naturally.

[0084] (7) Take the activated ceramic membrane in step (6) and place it in a vacuum drying oven for vacuum thermal activation at 300 °C for 2.2 hours to finally obtain a formed ceramic membrane with catalytic function. The average pore size is measured to be between 65 and 92 nm, and the product belongs to the ultrafiltration membrane.

[0085] Comparative Example 1

[0086] Refer to the scheme recorded in the reference journal literature "Desalination and Water Treatment" (https: / / www.sciencedirect.com / science / article / pii / S1944398624138908) to prepare a ceramic membrane product.

[0087] The main difference from the scheme of the present invention is that the raw materials used in this comparative example are pure γ-Al 2 O 3 and α-Al 2 O 3 , carboxymethyl cellulose (CMC, Merck) as a polymer binder, polyvinyl alcohol (PVA, Merck) as a dry chemical control additive, with an average pore size of 20.3 nm and almost no catalytic oxidation ability.

[0088] Comparative Example 2

[0089] Referring to the solution described in the patent document CN202411458234.0, a ceramic membrane product was prepared.

[0090] The main difference from the solution of the present invention is that the raw materials used in this comparative example are aluminum-containing sludge from a waterworks, corn starch, sawdust, coal powder, and polystyrene. The prepared ceramic membrane has the function of catalyzing the degradation of organic matter methylene blue by hydrogen peroxide, but the catalytic oxidation function is weak (in the presence of hydrogen peroxide of ~2 mol / L, the degradation of methylene blue is greater than 70% in 10 s); therefore, the weak catalytic function of the ceramic membrane is mainly used for self-cleaning, focusing on the filtration function and without the catalytic oxidation function.

[0091] The raw materials used in the present invention are aluminum-containing sludge from a waterworks during the algal bloom period, without other added materials. The product of the present invention is an ultrafiltration ceramic membrane (pore size ~60 nm) with both filtration and catalytic oxidation functions, and has excellent catalytic performance; in the presence of 1.34×10 - 4 mol / L of sodium hypochlorite, the contact time of 8 s can degrade ≥20% of the organic matter carbamazepine that is difficult to degrade by conventional oxidants.

[0092] Comparative Example 3

[0093] Purchased an ultrafiltration ceramic membrane product from a manufacturer in Nanjing, with the model number FCM-25.

[0094] The main difference from the solution of the present invention is that the product is an ultrafiltration ceramic membrane prepared with pure Al 2 O 3 as the raw material, and the pore-forming agent and other additives are unknown. This product only has the filtration function and no catalytic oxidation function.

[0095] The Third Part: Product Testing and Result Analysis

[0096] In the present invention, carbamazepine, a common refractory organic matter in water treatment and sewage treatment, is used as the test model for catalytic performance, and the concentration of carbamazepine is determined by high performance liquid chromatography. Sodium hypochlorite, the most commonly used oxidant in the ceramic membrane treatment process (10 mg / L), is used as the oxidant, and the reaction time simulates the contact time of 8 s during actual filtration.

[0097] The oxidation treatment method can almost treat all industrial wastewaters, especially suitable for treating organic matters that are difficult to be biodegraded in wastewater, such as most pesticides and insecticides, phenols, cyanides, and substances causing color and odor. Common oxidants used in water treatment include potassium ferrate, potassium permanganate, peracetic acid, chlorine dioxide, potassium monopersulfate, potassium persulfate, hydrogen peroxide, potassium percarbonate, chloramine, sodium hypochlorite, etc. However, these oxidants themselves will also remain in the water and are also a kind of pollutant that needs to be treated. Figure 2The figure shows the catalytic degradation performance diagrams of the ceramic membranes prepared in Example 1 for various oxidation reagents. It can be seen from this figure that the ceramic membranes of the present invention have significant removal capabilities for various oxidants; when using the ceramic membranes of the present invention, the removal rate of carbamazepine is significantly higher than the result under the condition of direct oxidation alone (the oxidant directly contacts and oxidizes carbamazepine without the participation of the ceramic membrane).

[0098] Take the ceramic membranes obtained in Example 1 and Comparative Examples 1 to 3, and conduct porosity, pore size distribution, and catalytic performance tests respectively. The porosity and pore size distribution are analyzed by a high-performance fully automatic mercury intrusion instrument. The performance test results of the examples and comparative examples are shown in Table 1.

[0099] Table 1

[0100]

[0101] It can be seen from the above test data that the ceramic membranes prepared by the present invention have good filtration performance, and their filtration pore sizes meet the requirements of ultrafiltration accuracy; at the same time, they have good performance in catalytic oxidation for removing trace harmful organic substances in water, and the first-order reaction rate constant is ~10 -2 s -1 . Relatively speaking, compared with the present invention, the performance of the products prepared by the prior art has almost no catalytic oxidation performance.

[0102] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various deformations or modifications within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing a ceramic membrane based on endogenous pore formation and catalysis of algae-containing sludge, characterized in that: The following steps are involved: (1) Dewatered sludge from a water supply plant during an algae outbreak is taken and dried, ball-milled and sieved to obtain sludge powder; (2) Using organic acid with complexing ability as a heavy metal remover, the sludge powder is soaked; then washed with deionized water and dried naturally; (3) Pre-carbonizing the air-dried sludge powder in an oxygen-free atmosphere; (4) forming the pre-carbonized sludge powder by dry pressing to prepare sludge green embryos; (5) heating the sludge green embryo and sintering it to obtain a membrane; (6) The sintered membrane is placed in a weak oxidizing strong acid and filtered in a circulation manner for preliminary activation treatment; then it is filtered in a circulation manner with deionized water and rinsed until the conductivity remains unchanged, and then taken out and air-dried at room temperature; (7) The air-dried membrane is heated under vacuum conditions for secondary activation to obtain an ultrafiltration ceramic membrane product.

2. The method according to claim 1, characterized in that In the step (1), the organic matter content of the sludge is 35% to 50%; the drying temperature is 105 to 120° C., and the drying time is ≥ 24 hours; the particle size of the sludge powder obtained by ball milling and sieving is in the range of 6.5 to 10 μm.

3. The method according to claim 1, characterized in that In the step (2), the organic acid is citric acid or oxalic acid with a mass concentration of 5.5% to 10%, and the soaking time is 24 to 36 hours.

4. The method according to claim 1, characterized in that: In the step (3), nitrogen or helium is continuously introduced into the tubular furnace to form an oxygen-free atmosphere; the temperature of the pre-carbonization treatment is 350-450° C., and the time is 3-5 hours.

5. The method according to claim 1, characterized in that In the step (4), during the dry pressing process, the pressure is controlled to be 20 to 25 MPa.

6. The method according to claim 1, characterized in that In the step (5), a heating controller is used to perform programmed temperature increase, the heating rate is 5 to 15° C. / min, the sintering temperature is 1000 to 1200° C., and the sintering time is 1.5 to 2 hours.

7. The method according to claim 1, characterized in that In the step (6), the strong acid used for the initial activation is hydrochloric acid with a concentration of 0.1 to 0.2 mol / L, and the activation treatment time is 3 to 4 hours.

8. The method according to claim 1, characterized in that In the step (7), the temperature during the secondary activation is 250-400° C., and the activation time is 2-2.5 hours.

9. A method for water treatment using an ultrafiltration ceramic membrane prepared by the method according to any one of claims 1 to 8, characterized in that: The ultrafiltration ceramic membrane is used as a filter element of a filtering device or a purification device; the drinking water, sewage or wastewater to be treated is introduced into the filtering device or the purification device, the water flow is filtered through the ultrafiltration ceramic membrane and the contact time during the actual filtration is guaranteed to be at least 8 seconds; while the micropores on the ultrafiltration ceramic membrane are used to intercept particulate pollutants, oxidant pollutants in the water are catalytically decomposed.

10. The method according to claim 9, characterized in that The oxidant pollutants refer to residual oxidants used for water treatment, specifically any one or more of the following: sodium hypochlorite, chlorine dioxide, chloramines, ozone, hydrogen peroxide, monopersulfate, peroxydisulfate, peracetic acid, sodium percarbonate, permanganate, and ferrate.

Citation Information

Patent Citations

  • Preparation method of self-cleaning ceramic membrane based on aluminum-containing sludge

    CN119345909A

  • Method for preparing zeolite water-supply sludge ceramsite for pretreating micro-polluted water

    CN102491729A

  • Micro-filtration ceramic membrane using waste materials as raw materials and preparation method thereof

    CN108546149A

  • Municipal sludge heat insulation sintered brick and preparation method thereof

    CN110002844A

  • Lightweight sludge ceramsite as well as preparation method and application thereof

    CN110698174A